Surface conditioning of a composite used for inlay/onlay restorations: Effect on μTBS to resin cement - Valandro, Luiz Felipe; Pelogia, Fernanda [UNESP]; Galhano, Graziela [UNESP]; Bottino, Marco Antonio [UNESP]; Mallmann, Andre (My University, 2007)
Purpose: To assess the effect of the composite surface conditioning on the microtensile bond strength of a resin cement to a composite used for inlay/onlay restorations. Materials and Methods: Forty-two blocks (6 × 6 × 4 mm) of a microfilled composite (Vita VMLC) were produced and divided into 3 groups (N = 14) by composite surface conditioning methods: Gr1 - etching with 37% phosphoric acid, washing, drying, silanization; Gr2 - air abrasion with 50-l̀m Al2O3 particles, silanization; Gr3 - chairside tribochemical silica coating (CoJet System), silanization. Single-Bond (one-step adhesive) was applied on the conditioned surfaces and the two resin blocks treated with the same method were cemented using RelyX ARC (dual-curing resin cement). The specimens were stored for 7 days in water at 37°C and then sectioned to produce nontrimmed beam samples, which were submitted to microtensile bond strength testing (μTBS). For statistical analysis (one-way ANOVA and Tukey's test, · = 0.05), the means of the beam samples from each luted specimen were calculated (n = 7). Results: μTBS values (MPa) of Gr2 (62.0 ± 3.9a) and Gr3 (60.5 ± 7.9a) were statistically similar to each other and higher than Gr1 (38.2 ± 8.9b). The analysis of the fractured surfaces revealed that all failures occurred at the adhesive zone. Conclusion: Conditioning methods with 50-l̀m Al2O3 or tribochemical silica coating allowed bonding between resin and composite that was statistically similar and stronger than conditioning with acid etching.
Keywords: Composite; Inlay; Microtensile bond strength; Surface conditioning; Tribochemical silica coating; aluminum oxide; bisphenol A bis(2 hydroxypropyl) ether dimethacrylate; dentin bonding agent; ESPE bonding system; macrogol derivative; phosphoric acid; polymethacrylic acid derivative; RelyX ARC; resin; resin cement; silane derivative; silicon dioxide; single bond; unclassified drug; water; adhesion; chemistry; dental acid etching; dental bonding; dental etching; dental surgery; human; materials testing; mechanical stress; surface property; temperature; tensile strength; Acid Etching, Dental; Adhesiveness; Aluminum Oxide; Bisphenol A-Glycidyl Methacrylate; Composite Resins; Dental Bonding; Dental Etching; Dentin-Bonding Agents; Humans; Inlays; Materials Testing; Phosphoric Acids; Polyethylene Glycols; Polymethacrylic Acids; Resin Cements; Silanes; Silicon Dioxide; Stress, Mechanical; Surface Properties; Temperature; Tensile Strength; Water